Sanitary conditions of few urban slums in New Delhi: a cross-sectional study - Husain, Safder; Khan, Noman; Raheem, Abdul; Urooj, Shaista; Siddiqui, Ziaul Haq (International Journal of Research in Medical Sciences, 2024)
Background: Sanitation is essential for a society’s well-being and general health. Water, sanitation, and hygiene standards that are both adequate and safe can prevent numerous infections in the context of the present study, which was conducted with the aim of spreading knowledge regarding water sanitation, disposal, and treatment in the urban slums of southeast Delhi to prevent and control several water-borne diseases. Methods: A cross-sectional study was conducted with 294 participants from 144 households, between May 2022 to April 2023. Data were collected using door-to-door surveys. The sample size was 294 and houses were selected using convenience sampling. The data obtained were analyzed using MS Office (Excel). Results: Based on data collected from 144 households and 294 participants, 44.2% of participants in the Trilokpuri area had an interrupted water supply. There was a significant correlation between the water supply groups in our analysis (p<0.0001). Conclusions: Our research revealed a strong correlation among sociodemographic profile, water supply, water usage, cleaning of water storage utensils, water stagnation, water disposal, treatment of stagnation, type of toilet, and sanitation conditions. According to the study’s key findings, the majority of people in southern Delhi did not have access to clean drinking water. There is obvious evidence of restricted access to contemporary piped water supplies. Thus, since drinking contaminated water can lead to a number of water-borne diseases, our research provides a framework for methodically raising awareness of the issues that need to be resolved to enable fair governance of the water supply.